Determinant of Islamic Insurance Performance in Indonesia: A GMM Approach - Dito Prakoso (Islamic Social Finance, 2021)
Profitability is an indicator in measuring the performance of a financial institution, one of which is sharia life insurance. Sharia life insurance profitability can be measured by Return on Assets (ROA). This study aims to analyze the influence of internal and external factors on the profitability of Islamic life insurance in Indonesia. The objects of this study were three full fledge and 15 sharia life insurance business units for the period 2014 to 2018. The research method used was panel data regression analysis dynamic generalized method of moments (GMM). The results showed that leverage and contribution (premium) had a positive and significant effect on the profitability of sharia life insurance.